2021
DOI: 10.21031/epod.944067
|View full text |Cite
|
Sign up to set email alerts
|

Item Wording Effects in Psychological Measures: Do Early Literacy Skills Matter?

Abstract: While the inclusion of both positively and negatively worded items is a common practice in scales, using positively and negatively worded items together may threaten the validity of a scale. Several studies have been devoted to investigating the effects of item wording methods. The current study investigated item wording effects on the responses of 4028 Turkish fifth-grade students, who responded to the Students Confidence in Mathematics (SCM) and Students Confidence in Science (SCS) scales. The role of early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…More exactly, regardless of which reversal strategy is used, the reverse items caused an artificial factor that can also be called a method factor in addition to the trait factor. Consistent with this result, many studies in the literature revealed that reverse items in scales measuring a single unitary construct distort the factor structure of the scale by generating a separate dimension, which leads to an unintentionally multidimensional factor solution (Bulut & Bulut;DiStefano & Motl, 2006;Dunbar et al, 2000;Hazlett-Stevens et al, 2004;Herche & Engelland, 1996;Knight et al, 1998;Pilotte & Gable, 1990;Spector et al, 1997).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…More exactly, regardless of which reversal strategy is used, the reverse items caused an artificial factor that can also be called a method factor in addition to the trait factor. Consistent with this result, many studies in the literature revealed that reverse items in scales measuring a single unitary construct distort the factor structure of the scale by generating a separate dimension, which leads to an unintentionally multidimensional factor solution (Bulut & Bulut;DiStefano & Motl, 2006;Dunbar et al, 2000;Hazlett-Stevens et al, 2004;Herche & Engelland, 1996;Knight et al, 1998;Pilotte & Gable, 1990;Spector et al, 1997).…”
Section: Discussionmentioning
confidence: 77%
“…Indeed, Schmitt and Allik (2005) and Hooper et al (2013) disclosed that reverse items were interpreted differently across countries. The mentioned contradiction may also be associated with the sample characteristics because the factors such as reading achievements (Bulut & Bulut, 2022;Michaelides, 2019), age levels (Bulut, 2021;Marsh 1986) and cognitive abilities (Gnambs & Schroeders, 2020) The results of the study indicated that internal consistency coefficient of Form-RN was lower than that of the other two versions. The facts that the reliability coefficient of Form-RN is lower than that of Form-P are coherent with those found by other researchers (Bourque & Shen, 2005;Carlson, 2011;Coleman, 2013;Ebesutani et al, 2012;Johnson et al, 2004;Roszkowski & Soven, 2010;Salazar, 2015;Suárez-Alvarez, 2018).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation